Parental involvement in children’s education: A study among Muslim minority - Yahefu, Humaer; Badrasawi, Kamal J I; Khalid, Madihah (2017)
Parental involvement plays a substantial role in children’s all-round personality development. In Islam, parents are responsible to raise their children and the parents will be asked about the fulfillment of this responsibility. Parental involvement in children’s education among Muslim Minority in China is highly demanded. Hence, this paper aims to identify the level of parental involvement in children education at a rural area with Muslim minority in China. The cross-sectional survey design was employed. Three hundred and thirty nine (339) students were randomly selected from grades two to five (2-5) to answer a questionnaire on parental involvement (i.e. aspiration, home-based and school-based involvement). Means, standard deviations, and correlation, and independent sample t-test were used in the data analysis. The results showed that the Muslim parents had quite high level of parental involvement in their children education as indicted by the parental involvement mean scores. However, parents were least involved in the activities conducted at school. There was a statistically significant positive correlation between parental involvement and students’ academic achievement. However, there was no statistically significant difference in parental involvement due to student gender. The parents’ low proficiency in the Chinese language and their low academic qualifications might be challenges to parents’ involvement. In conclusion, Muslim parents were highly inspired to be involved in their children education. Further qualitative and quantitative research could be conducted to examine the effectiveness of parental involvement methods and the challenges to Muslim parents’ involvement.